Growth Of Female New Zealand Crossbreed Rabbit On Variation Of Feed Protein Level - Soedjadi, Soedjadi; Haryanto, B; Sodiq, A (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 1999)
The Growth of Female New Zealand White Crossbreed Rabbit on Variation of Feed Protein Level have studied on Experimental Farm Animal Husbandry Faculty, University of Jenderal Soedirman Purwokerto.Â Â On â Station Research by Factorial Pattern based on Two-Way Classification Design, were involved 42 heads rabbit two months of age. Factors examine consistÂ of : kinds of feed as a first factors (a1 = without fish meal, a2 = fish meal 2%, a3 = fish meal 12%, a2 = fish meal 22%), and body weight as a second factors (b1 = 601-700 gram,b2 = 701-800 gram, b3 = 801-900 gram). Variance analysis showed that there were significance (P< 0.01) interaction between kinds of feed and body weight on daily gain and feed consumption. Increasing feed protein level (2, 12 and 22% of fish meal) clearly increase (P<0.01) of daily gain and feed consumption on overall of body weight conditionsÂ (b1,b2 and b3). Daily gain and feed consumption really affected (P<0.01) by body weight on overall of feed protein level. (Animal Production 1(1) : 30-35 (1999).Â Â Key Words : Growth, Rabbit, Protein